(untitled) (Baltic Journal of Sport and Health Sciences, 2017)
Background. Fish oil contains essential fatty acids that are linked to better cardiovascular health and even the prevention of sudden cardiac death in athletes. The purpose of this work was to examine the effects of 90 days of fish oil supplementation in elite-, leisure-, and non-athletes on body fat percent, body mass index (BMI), blood cholesterol and triglycerides, heart rate and blood pressure, and on exercise performance. Method. Three groups of participants were tested with 12 equally distributed men and women in each: elite- athletes, leisure-athletes, and non-athletes. Participants received body weight-adjusted commercially available fish oil over 90 days. These nutritional supplements were taken in the morning, immediately following breakfast. Results. The findings revealed that compared to the baseline, body fat percent decreased in all the three groups (p = .034), however, blood cholesterol and the cholesterol/high density lipoprotein (HDL) ratio increased (p < .05), with the elite-athletes showing the largest increase. Exercise performance, in terms of the time of running to voluntary exhaustion, increased (p = .05), but the largest benefits were observed in non-athletes (22%) in contrast to leisure- athletes (4%) and elite-athletes (1%), which could be linked to a ceiling effect. No statistically significant changes were observed in any other anthropometric, physiological, or biochemical measures. Conclusion. These findings suggest that 90 days of fish oil supplementation may benefit body composition and increase exercise performance, especially in non-athletes, and increases cholesterol, as well as cholesterol/HDL ratio levels, primarily in elite-athletes. Based on these results, it appears that fish oil supplementation yields greater benefits in non-athletes than in athletes. Keywords: anthropometric measures, biochemical measures, body composition, in-situ, real life setting.